On a Question of Definition of a Phenomenon of Diaspora (on the Example of the Armenian Diaspora of the Russian Federation) - K. K. Tirabian (North-West institute of management of the Russian Presidential Academy of National Economy and Public Administration, 2018)
The article examines the role of the diaspora in the political processes of the state. As an example, the Armenian Diaspora is located on the territory of the Russian Federation. The main approaches to determining the phenomenon of «diaspora» by well-known domestic and foreign scientists are considered. Key characteristics of classical and modern diasporas, as well as modern approaches to the phenomenon of «diaspora»: sociological, political and ethnic, are presented. The author analyzes the reasons for the resettlement of Armenians from their historical homeland. The main periods of formation of the Armenian diaspora in Russia are outlined. The author defines the stages of formation and development of the Armenian diaspora in Russia. The role of the Armenian Diaspora at the present stage is highlighted. The research reveals the main directions and tasks of the Armenian Diaspora. The role of the Diocese of the Armenian Apostolic Church in the life of the Armenian Diaspora in the Russian Federation is noted.